(untitled) (Agricultural Engineering, 2018)
The methods currently used to assess orchard infestation are time-consuming and do not take into account non-adult forms of mites, due to their small size. Advance in digital imaging technology, however, has resulted in the discovery of a more viable method to enable a fast and reliable assessment of orchard infestation. Digital images of infected apple leaves were made and examined for the presence of European red mites and two-spotted spider mites. As well as adult mites, non-adult European red mite forms were also encountered. After extracting all objects considered as mites from the image, imaging software was then used to assess their dimension and shape parameters. Length, width, area, and equivalent diameter were different for all three observed mite groups: adult female European red mites, possible non-adult European red mites and adult two-spotted spider mites. Differences in circularity and elongation were found in adult two-spotted spider mites and various forms of European red mites, while the perimeter was similar in adult European red mites and two-spotted spider mites, and different in the non-adult forms of European red mites. However, as the ranges of 95% prediction intervals for these features overlap, a combination of at least two features as well as employing statistical procedures may greatly increase the probability of appropriate classification of the observed objects as different mites.